Flourishing Pada Mahasiswa Yang Mengikuti Organisasi Kemahasiswaan Ditinjau Dari Spiritualitas Dan Dukungan Sosial - Maya Destalia; Iin Yulianti; Nugroho Arief Setiawan (IDEA: Jurnal Psikologi, 2024)
Flourishing is an important construct for students to have, because it has a positive impact or influence on them. These impacts include the good influence of flourishing on academic achievement and improving student performance. This research aims to determine the relationship between spirituality and social support and the flourishing of students who join student organizations. This research uses a correlational quantitative approach with 92 students as respondents who are currently actively participating in student organizations. The instruments used in this research were the flourishing scale (α = 0.832), the spirituality scale (α = 0.936) and the social support scale (α = 0.900). The data collection technique uses non-probability sampling techniques, especially purposive sampling techniques. In analyzing the data, researchers used multiple linear regression test techniques. The research results show that there is a relationship between spirituality and social support and the flourishing of students who join student organizations.